Development of a deep learning-based approach for remaining useful life prediction of turbofan engine - Ng, Yi Hong (Nanyang Technological University, 2023)
In recent times, there has been a growing interest in predictive maintenance for turbofan engines as it has demonstrated significant potential in improving the maintenance process. The core concept behind predictive maintenance is to predict the remaining useful life (RUL) of a system. With accurate RUL predictions, the maintenance process can be optimised in terms of the maintenance frequency and resources consumed. This leads to considerable cost-savings without compromising the reliability and safety of the system.